2001
DOI: 10.1159/000054912
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Regional [<sup>14</sup>C]2-Deoxyglucose Uptake in Response to Long-Term Clozapine Administration in Rats

Abstract: Clozapine has superior effects in treating negative symptoms of schizophrenia and causes less extrapyramidal side effects than traditional antipsychotics. In this study, we investigated the effects of acute and long-term clozapine administration on [14C]2-deoxyglucose uptake (2-DG uptake) in rats, as measured using the [14C]2-deoxy-D-glucose method. The 2-DG uptake was reduced in fewer regions after chronic clozapine (46%) than after acute clozapine (97%). After chronic clozapine treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our patients were studied under a "resting" cognitive condition, but other authors using a standard cognitive activation paradigm also reported lower prefrontal activity following clozapine treatment with respect to fluphenazine-treated (Cohen et al 1997) or placebo-treated (Potkin et al 2003) patients. The metabolic decrease in the PF region agrees with observed effects in animal pre-clinical studies after acute (Tsai et al 2001;Cochran et al 2002) and chronic (Tsai et al 2001) clozapine administration.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our patients were studied under a "resting" cognitive condition, but other authors using a standard cognitive activation paradigm also reported lower prefrontal activity following clozapine treatment with respect to fluphenazine-treated (Cohen et al 1997) or placebo-treated (Potkin et al 2003) patients. The metabolic decrease in the PF region agrees with observed effects in animal pre-clinical studies after acute (Tsai et al 2001;Cochran et al 2002) and chronic (Tsai et al 2001) clozapine administration.…”
Section: Discussionsupporting
confidence: 86%
“…Along the same lines, Tsai et al (2001) have reported a decrease of glucose metabolism in thalamic, limbic, and cortical (including PF) regions in rats following acute and chronic clozapine treatment.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Because CLZ has high uptake in the rat brain, with a brain-to-plasma ratio of 24:1, even low doses of CLZ may induce off-target effects via concurrent action at endogenous CLZ targets 11 . In addition, CLZ is known to influence metabolic activity in multiple areas of the brain 12,13 . Therefore, it is important to find the lowest dose of CLZ that will activate DREADDs while minimizing off-target effects.…”
mentioning
confidence: 99%
“…27 Clozapine has also been observed to reduce glucose uptake into brain regions, especially the extrapyramidal system and thalamus after acute exposure. 28 Although the mechanism is incompletely understood, these results clearly indicate that clozapine can inhibit glucose uptake through GLUT proteins from brain and peripheral tissue. Such research is important in trying to understand the mechanism by which the atypical antipsychotic drugs produce hyperglycaemia in vivo.…”
Section: Mechanism Of Association Of Atypical Antipsychotic Drugs Witmentioning
confidence: 98%